RESPON PERTUMBUHAN DAN HASIL TANAMAN PADI (Oryza sativa L.) TERHADAP KEBUTUHAN NITROGEN MENGGUNAKAN BAGAN WARNA DAUN - Rizka Laila Ali Abu; Zainuddin Basri; Usman Made (Universitas Tadulako, 2017)
This study aimed to findthe method that can determine the right amount of nitrogen need using either a conventional technique or a leaf color chart and to determine the rate of nitrogen better for rice plant growth and yield. The study used a two factorial experimental design. Those factors were three rates of fertilizers and two kinds of fertilizer applications. The rate of fertilizer needed by the plant was either 200 kg ha-1 as suggested by the leaf color method or 250 kg ha-1 as shown by the conventional method. Based on the plant height and percent of empty grain, the leaf color chart method is better in determining the amount of nitrogen needed by the plant. The addition of 250 kg ha-1 nitrogen tends to decrease the percent of empty grains. Keywords: Leaf color chart, Nitrogen, and Rice.